DEVELOPMENT OF TEACHING MATERIALS INTEGRATED WITH CULTURAL VALUES IN SMA KABUPATEN ACEH BESAR - Syahrul Riza (SENSEI RESEARCH CENTER, 2021)
Learning tools play an important role and become a reference for teachers in schools. In this case, the importance of developing teaching materials is equally important in the development of learning devices because teaching materials are part of learning devices so that teachers are required to have the ability to develop their own learning tools. The purpose of this study was to develop Islamic religious education teaching materials through a sociocultural approach to high school students in Aceh Besar. This research was conducted using a qualitative approach. Qualitative research is research that describes the data obtained in the field. Information that has been obtained in the field either through direct observation, interviews, document review, and official records at each school that is the object of research. The research results found that; The development of Islamic Religious Education (PAI) teaching materials is by integrating cultural values with Islamic Religious Education (PAI), starting with the search for cultural values which are then collected to understand the meaning contained in them through competent literatures and cultural figures. in the field; the development of PAI teaching materials based on social and cultural references is by looking at the local wisdom of the local culture. In this research, the local wisdom raised is about hadih maja; the development of Islamic Religious Education (PAI) teaching materials that accommodate socio-cultural values or local culture (local genius) is by combining the material in the RPP with local wisdom material in Aceh Besar.